1992
DOI: 10.1037/h0088260
|View full text |Cite
|
Sign up to set email alerts
|

Testing models of school learning: Effects of quality of instruction, motivation, academic coursework, and homework on academic achievement.

Abstract: Tested the influence of ability, time, quality of instruction, motivation, and academic coursework on high school students' achievement, also controlling for relevant background variables. Structural equation models were analyzed with longitudinal data from a national sample. Intellectual ability and academic coursework had powerful direct effects on achievement, and homework had a smaller direct effect. The indirect effects of quality of instruction and motivation were stronger than their direct effects; qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(53 citation statements)
references
References 39 publications
1
48
0
4
Order By: Relevance
“…This study found that more time spent on homework resulted in higher achievement. Similarly, results from Keith and Cool's (1992) quantitative study using 25,875 high school students from the 1980 and 1982 NCES High School and Beyond Longitudinal Studies revealed that time spent on homework had an important and meaningful influence on achievement and learning. In his review of literature, Cooper (1994) also discovered that out of 50 studies correlating time spent on homework with achievement, 43 showed that students who did more homework had better achievement.…”
Section: Does Homework Help?mentioning
confidence: 99%
“…This study found that more time spent on homework resulted in higher achievement. Similarly, results from Keith and Cool's (1992) quantitative study using 25,875 high school students from the 1980 and 1982 NCES High School and Beyond Longitudinal Studies revealed that time spent on homework had an important and meaningful influence on achievement and learning. In his review of literature, Cooper (1994) also discovered that out of 50 studies correlating time spent on homework with achievement, 43 showed that students who did more homework had better achievement.…”
Section: Does Homework Help?mentioning
confidence: 99%
“…For instance, students who attend an advanced course in mathematics or an elite school might spend more time on mathematics homework than students enrolled in a basic course or a lower level school (see Keith & Cool, 1992). Likewise, more homework might be set in high-quality schools attended by students from privileged backgrounds.…”
mentioning
confidence: 97%
“…In addition, the analysis showed that within the positive results, the positive relationship was much stronger for secondary students (students in Grades 7-12) than for elementary school students, suggesting that older students differ from younger students in the benefits they derive from homework. One of the more extensive studies reporting a positive association between time spent and outcomes is Keith and Cool's (1992) structural equation modeling study of academic achievement in high school students. This study examined the effects of several predictors-intellectual ability, quality of instruction, academic motivation, quantity of academic coursework, and time spent on homework-on a composite measure of achievement that included reading, math, science, writing, and civics standardized test scores.…”
Section: Time Spent On Homeworkmentioning
confidence: 99%